2022
DOI: 10.1002/lno.12086
|View full text |Cite
|
Sign up to set email alerts
|

Tight association between microbial eukaryote and giant virus communities in the Arctic Ocean

Abstract: Viruses are important regulatory factors of the marine microbial community including microeukaryotes. However, little is known about their role in the northern Chukchi Sea in the Arctic basin, which has oligotrophic conditions in summer. To clarify the link between microbial eukaryotic communities and viruses as well as environmental conditions, we investigated the community structures of microeukaryotes (from 3 to144 μm and from 0.23 μm size bio‐particles collected from seawater) and Imitervirales (from 0.23 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2
1

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 80 publications
0
3
0
Order By: Relevance
“…Most of the members of modules 5 and 6 were Dinoflagellata (mainly MALV-I and MALV-II), but modules 2 and 3 also contained some Arthropoda (zooplankton) as the members. The read counts of zooplankton OTUs seemed not to reflect the relative abundance of adult animals, but relate to their debris, eggs, or feces, considering the size fractions of samples [ 42 ]. The members of module 4 consisted of half Dinoflagellata and half a variety of other taxa.…”
Section: Resultsmentioning
confidence: 99%
“…Most of the members of modules 5 and 6 were Dinoflagellata (mainly MALV-I and MALV-II), but modules 2 and 3 also contained some Arthropoda (zooplankton) as the members. The read counts of zooplankton OTUs seemed not to reflect the relative abundance of adult animals, but relate to their debris, eggs, or feces, considering the size fractions of samples [ 42 ]. The members of module 4 consisted of half Dinoflagellata and half a variety of other taxa.…”
Section: Resultsmentioning
confidence: 99%
“…In the ocean, viruses are the most abundant biological entities 6 and play important roles in the regulation of microbial host communities, carbon and nutrient cycling, and horizontal gene transfer among organisms 710 . Recent metagenomic studies have revealed that both Arctic 11,12 and Antarctic 13,14 environments harbour diverse viruses, with an elevated diversity of prokaryotic dsDNA viruses in the Arctic Ocean 11 . A large proportion of Arctic-specific genes from these viruses were suggested under positive selection based on their mutation patterns.…”
Section: Mainmentioning
confidence: 99%
“…Recent metagenomic studies have revealed that both Arctic 11,12 and Antarctic 13,14 environments harbour diverse viruses, with an elevated diversity of prokaryotic dsDNA viruses in the Arctic Ocean 11 . A large proportion of Arctic-specific genes from these viruses were suggested under positive selection based on their mutation patterns.…”
Section: Mainmentioning
confidence: 99%